2011
DOI: 10.1007/s11626-011-9427-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender-specific adult bovine serum on myogenic satellite cell proliferation, differentiation and lipid accumulation

Abstract: Gender specificity in muscle growth and development is well known. Genesis of muscle is dependent on proliferation and differentiation potential of resident myogenic satellite cells (MSCs) present in muscle fibers. Multipotential capacity of forming myocyte, osteocyte, and adipocyte like cell makes MSCs a unique stem cell. To understand the molecular mechanism involved in determination of muscle quality due to difference in hormone concentration of different gender of animals, MSCs were isolated from bovine sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…MSCs are stem cells that reside between the sarcolemma and the basal lamina of adult skeletal muscle [71]. Since the serum derived from bovine species is an essential component of the in vitro cell culture system, there would be a great advantage of using bovine primary MSCs that closely mimic the in vivo situation during myogenesis [72]. Indeed, such studies might enable enhancement of muscle fiber characteristics, leading to improved meat quality.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are stem cells that reside between the sarcolemma and the basal lamina of adult skeletal muscle [71]. Since the serum derived from bovine species is an essential component of the in vitro cell culture system, there would be a great advantage of using bovine primary MSCs that closely mimic the in vivo situation during myogenesis [72]. Indeed, such studies might enable enhancement of muscle fiber characteristics, leading to improved meat quality.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures of bovine MSCs in media containing fetal bovine serum obtained from the same species may have an added advantage because they can mimic the in vivo environment more closely [21]. Identification of many genes differentially expressed during MFCs formation and ALCs formation using microarray analysis in association with the primary bovine MSCs culture system and validation of the physiological role of each gene support this idea [6,20,33].…”
Section: Discussionmentioning
confidence: 99%
“…To induce differentiation, cells were allowed to grow in DMEM without reducing serum (DMEM with 10% FBS and 1% P/S). A detailed description of MSCs isolation, differentiation, and transdifferentiation is described in our previous studies [6,21]. Cells were harvested for RNA isolation on day 10 of culture for MSCs and day 14 for MFCs.…”
Section: Methodsmentioning
confidence: 99%
“…In another reports, horse serum was shown to be more effective than FBS for the differentiation of adipogenic stem cells into adipocytes (5,6). Recently, we also showed that adult bovine serum (ABS) has the capacity to regulate lipid accumulation in myogenic precursor cells during trans-differentiation into adipocytes (7). In addition, ABS and FBS were characterized to possess different contents of lipids, proteins and hormones, although serum constituents could not be fully defined (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we also showed that adult bovine serum (ABS) has the capacity to regulate lipid accumulation in myogenic precursor cells during trans-differentiation into adipocytes (7). In addition, ABS and FBS were characterized to possess different contents of lipids, proteins and hormones, although serum constituents could not be fully defined (7,8). These results have suggested that ABS may contain a distinct serum factor that regulates the differentiation of adipogenic precursor cells (8).…”
Section: Introductionmentioning
confidence: 99%